Moderatisme sebagai Konsep Berkehidupan Bersama dalam Perspektif Tafsir Al-Qur’an Kontemporer - Landy Trisna Abdurrahman (Lajnah Pentashihan Mushaf Al-Qur'an, 2022)
In fact, there are still many people who are not ready to live with other different groups. The whites still don't want to live with the blacks. In Indonesia, Muslims are not ready to live with people of other religions. Violations of freedom of religion and belief in Indonesia throughout 2019 reached more than 215 cases. In America, three black Muslims was killed by a white neighbor. In fact, religion based on belief can also be a critique of social problems, including the problem of live together, and Islam is a religion based on belief, sourced from revelation. The interpretation of revelation (Al-Qur'an) has a very important role to form the basis for behavior to realize a peaceful life together: be moderate. This article tries to explore contemporary interpretations of the interpretation of the words moderate and live together in the Qur'an. This research is a qualitative research with data sources from various contemporary interpretations. This article finds that the goal that must be achieved in live together is to maintain peace. Meanwhile, being moderate is a process of dialogue between various differences and interests that exist in humans. Moderate behavior can only be achieved with an open mind and without suspicion of differences.